2017
DOI: 10.1021/jacs.7b01982
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Push–Pull Hypothesis: Lewis Acid Augmented N2 Activation at Iron

Abstract: We present a systematic investigation of the structural and electronic changes that occur in an Fe(0)–N2 unit (Fe(depe)2(N2); depe = 1,2-bis(diethylphosphino)-ethane) upon the addition of exogenous Lewis acids. Addition of neutral boranes, alkali metal cations, and an Fe2+ complex increases the N–N bond activation (Δ νNN up to 172 cm−1), decreases the Fe(0)–N2 redox potential, polarizes the N–N bond, and enables −N protonation at uncommonly anodic potentials. These effects were rationalized using combined expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

16
186
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(217 citation statements)
references
References 53 publications
(52 reference statements)
16
186
2
1
Order By: Relevance
“…[7] Tris(pentafluorophenyl)borane has also been used as an excellent activator for metallocene Ziegler-Natta catalysts. [13][14][15] Recently, it was also found by Szymczak [16] and Simonneau [17] that B(C 6 F 5 ) 3 can interact with N 2 containing transition complexes. [13][14][15] Recently, it was also found by Szymczak [16] and Simonneau [17] that B(C 6 F 5 ) 3 can interact with N 2 containing transition complexes.…”
mentioning
confidence: 88%
“…[7] Tris(pentafluorophenyl)borane has also been used as an excellent activator for metallocene Ziegler-Natta catalysts. [13][14][15] Recently, it was also found by Szymczak [16] and Simonneau [17] that B(C 6 F 5 ) 3 can interact with N 2 containing transition complexes. [13][14][15] Recently, it was also found by Szymczak [16] and Simonneau [17] that B(C 6 F 5 ) 3 can interact with N 2 containing transition complexes.…”
mentioning
confidence: 88%
“…[12] While this paper was being written, Szymczak and co-workers reported, in av ery elegant but contextually different study,t hat adduct formation of 2 with the [(depe) 2 Fe(N 2 )] complex (depe = 1,2-bis(diethylphosphino)ethane) enhances activation of the dinitrogen ligand (Scheme 1, bottom). [13] We treated orange C 6 D 6 suspensions of 1 with 1equivalent of 2 at room temperature and immediately obtained dark green solutions.S pectroscopic analysis indicated the clean formation of new complexes 3, according to 1 H, 31 P, 19 Fand 11 BNMR spectroscopy (! 90 % NMR yield;S cheme 2).…”
mentioning
confidence: 99%
“…Repeating these experiments on al arger scale in toluene or chloroben- zene,followed by addition of pentane caused precipitation of dark powders (see the Supporting Information for details) from which single crystals suitable for an X-ray diffraction study could be grown. [13] Compounds 3 Mo and 3 W can be viewed as zero-valent Group 6m etal/B(C 6 F 5 ) 3 TMFLP templates that activate dinitrogen. Themolecular structures of adducts 3 Mo and 3 W given in Figure 1a re quite similar.…”
mentioning
confidence: 99%
“…1.748 (8) 8,15 Collectively these data correlate with an enhanced transfer of electron density from Fe into the NN fragment upon electrophilic attack at the terminal nitrogen (N β ), which results in an increased Fe-N bond order attendant with a reduction in the N-N bond order. Recently, the borane adduct Fe(depe) 2 (NN·B(C 6 F 5 ) 3 ) has been structurally verified, 16 which permits a valuable comparison between electrophiles of differing Lewis acidity upon the extent of electron transfer from Fe to N 2 , using the same parent system 1. The lower IR stretching frequencies 17 (Table 1; see ESI for full details), although with slightly more obtuse N-N-Si bond angles than those observed from X-ray diffraction data.…”
mentioning
confidence: 99%
“…Using a Walsh-type analysis, it was shown that this interaction is optimised for a bent rather than linear N-N-B bond angle, as this maximises overlap between the B p-orbital and a lobe of the N 2 π* MO; for the B(C 6 F 5 ) 3 adduct this was experimentally determined to be 137.0(3)°. 16 The experimental and theoretical trends in N-N-R bond angles for the [Fe(PP) 2 …”
mentioning
confidence: 99%